Timing of respiratory syncytial virus and influenza epidemic activity in five regions of Argentina, 2007-2016 - Baumeister, Elsa (2019)
Fil: Baumeister, Elsa. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Virosis Respiratoria; Argentina.